2009
DOI: 10.1007/s00467-008-0969-9
|View full text |Cite
|
Sign up to set email alerts
|

Urine macrophage migration inhibitory factor (MIF) in children with urinary tract infection: a possible predictor of acute pyelonephritis

Abstract: Macrophage migration inhibitory factor (MIF) is an important pro-inflammatory cytokine expressed at sites of inflammation. We have assessed this factor (MIF) in urinary tract infections with the aim of determining a non-invasive and sensitive method to differentiate upper and lower renal involvement. Thirty-three pediatric patients with urinary track infection (25 with acute pyelonephritis, eight with acute cystitis) and 40 healthy subjects were recruited for this prospective case-control study. Pyelonephritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
3
12
0
1
Order By: Relevance
“…We found that the urinary MIF level is a more sensitive indicator of kidney injury than the systemic MIF level, as suggested by Brown et al [17, 18]. Previous studies have focused on the use of elevated urinary MIF levels to detect the presence of UTIs and to distinguish kidney infections from acute cystitis [23, 24]. In patient with normal renal function, consistent with previous study, our study revealed that elevated urinary MIF indicated the presence of APN.…”
Section: Discussionsupporting
confidence: 73%
“…We found that the urinary MIF level is a more sensitive indicator of kidney injury than the systemic MIF level, as suggested by Brown et al [17, 18]. Previous studies have focused on the use of elevated urinary MIF levels to detect the presence of UTIs and to distinguish kidney infections from acute cystitis [23, 24]. In patient with normal renal function, consistent with previous study, our study revealed that elevated urinary MIF indicated the presence of APN.…”
Section: Discussionsupporting
confidence: 73%
“…This is in agreement with Otukesh et al [28], who studied urinary MIF in 25 children with acute pyelonephritis, 8 children with acute cystitis, and 40 controls without UTI. He used a cut-off point of uMIF/Cr > 4.89 pg/μmol to differentiate upper from lower UTI and found a sensitivity and specificity of 92% and 100%, respectively.…”
Section: Ahmed J Al-sayyad Salah M El-morshedy Ehab a Abd Al Hamidsupporting
confidence: 91%
“…In our study, uMIF/Cr was significantly higher in patients with leukocytosis (p=0.0001) and a positive CRP level in the serum (p=0.003) ( Table 2). Otukesh et al found that urinary MIF/Cr levels can be used to differentiate between upper and lower UTI in children [20]. In this study, 25 children with acute pyelonephritis, eight children with acute cystitis and 40 controls without UTI were compared; a uMIF/Cr >4.89 pg/µmol was determined to be the cut-off point for differentiating upper from lower UTI.…”
Section: Discussionmentioning
confidence: 99%